(untitled) (Bangladesh Heart Journal, 2024)
Background: Acute ST-elevated myocardial infarction is a life-threatening condition. Presence of fragmented QRS (fQRS) after acute STEMI is associated with alteration of myocardial activation due to myocardial scar and myocardial fibrosis. Previous studies have suggested that fQRS in acute STEMI is associated with increased mortality, morbidity, sudden cardiac death and recurrent adverse cardiovascular events. The study was designed to assess the association of fQRS complex with short-term outcome (in hospital and 30 days follow up) in patients with acute ST elevation myocardial infarction. Methods: This prospective cohort study was conducted in the Department of Cardiology, Dhaka Medical College Hospital among the STEMI patients who were thrombolysed. All patients underwent serial ECG at admission, within first 12 hours, at 24 hours and at 48 hours for detecting the presence of fQRS complex. Patients showing fQRS involving infarct territory within 48 h of admission were included in the “fQRS group” and those who did not develop fQRS within 48 h of admission were included in the “without fQRS” group. 114 patients had fQRS complex and 104 patients were without fQRS in their ECG. In-hospital outcomes such as: death, heart failure, significant arrhythmias (VT, VF AF, SVT, 20 AV block, CHB), cardiogenic shock were recorded. Among the study patients, sixteen patients were lost to follow up in 30 days of index hospitalization. Finally, 202 patients were tracked for follow up regarding death or re hospitalization information by personal contact or over telephone. Statistical analysis was performed using the statistical package for social science (SPSS) 21.0 software for windows. Results: Appearance of fQRS complex occurred at admission, within first 12 hours, 24 hours and 48 hours in 53.5%, 23.7%, 14.9% and 7.9% cases respectively. During index hospitalization, development of cardiogenic shock (27.19% vs 11.54%), heart failure (23.68% vs 9.62%) and significant arrhythmias were significantly higher in fQRS group (42.10% vs 11.53%, p<0.05). Although mean duration of hospitalization was similar in both groups (p>0.05), but in-hospital mortality was higher in fQRS group (11.40% vs 3.85%, p<0.05). Rate of re-hospitalization was significantly higher in patients with fQRS complex (21.69% vs 7.29% p<0.05). Overall mortality within 30 days of index hospitalization follow-up also differs significantly in presence of fQRS complex (19.81% vs 5.2%; p =0.006). Conclusion: Presence of fQRS complex is associated with adverse short-term outcome in patients with acute ST elevation myocardial infarction. Hence, these patients need more aggressive and early invasive treatment to reduce morbidity and mortality. Bangladesh Heart Journal 2024; 39(2); 93-101